Anchorage Design for Petrochemical and Other Industrial Facilities Second Edition. - Design, Task Committee on Anchorage (American Society of Civil Engineers, 2022)
This book intends to serve as a source for uniformity in the design, fabrication, and installation of anchorage in petrochemical and other industrial facilities.
Keywords: Petroleum refineries -- Design and construction.; Industrial buildings -- Foundations.; Wind-pressure.; elektronické knihy; electronic books